Ki-67 protein: a proliferation index in breast cancer - Shervin Kheirandish (Reviews in Clinical Medicine, 2015)
Various clinicopathological factors are evaluated in different studies on carcinomas to demonstrate their prognostic and predictive significance during the diagnosis and therapeutic procedures of the malignancy. Ki-67 is a biomarker that was proposed as a cell proliferation related nuclear antigen, and it only expresses in growing and proliferating cells. This unique feature of Ki-67 makes it a subject of interest in different investigations. Evaluating the Ki-67 expression has been demonstrated to be beneficial in determining the tumor behavior including tumor size, stage, grading and patient survival. Moreover, it might be helpful in selecting the preferred subsequent treatment strategy. Due to the importance of Ki-67 index, we aim to briefly review its properties and the importance of its expression during various types of malignancies. At last, the prognostic and predictive value of Ki-67 would be overviewed regarding the efficacy of neoadjuvant and adjuvant therapies in breast cancer patients.